mxCSM: A 100-slit, 6-Wavelength Wide-Field Coronal Spectropolarimeter for the Study of the Dynamics and the Magnetic Fields of the Solar Corona - Lin, Haosheng (Frontiers in Astronomy and Space Sciences, 2016)
remendous progress has been made in the field of observational coronal magnetometry in the first decade of the 21st century. With the successful construction of the Coronal Multichannel Magnetometer (CoMP) instrument, observations of the linear polarization of the coronal emission lines (CELs), which carry information about the azimuthal direction of the coronal magnetic fields, are now routinely available. However, reliable and regular measurements of the circular polarization signals of the CELs remain illusive. The CEL circular polarization signals allow us to infer the magnetic field strength in the corona, and is critically important {\bf of} our understanding of the solar corona. Current telescopes and instrument can only measure the coronal magnetic field strength over a small field of view. Furthermore, the observations require very long integration time that preclude the study of dynamic events even when only a small field of view is required. This paper describes a new instrument concept that employees large-scale multiplexing technology to enhance the efficiency of current coronal spectropolarimeter by more than two orders of magnitude. This will allow for the instrument to increase of the integration time at each spatial location by the same factor, while also achieving a large field of view coverage. We will present the conceptual design of a 100-slit coronal spectropolarimeter that can observe six coronal emission lines simultaneously. Instruments based on this concept will allow us to study the evolution of the coronal magnetic field even with coronagraphs with modest aperture.